Examples in the classroom: pattern classification using the r language (2012)
In many courses with a strong mathematical background, students often experience difficulties when concepts are put into practice to solve problems. In our teaching experience, the R language for statistical computing is a powerful tool for exemplifying algorithms, solving numerical problems, and illustrating concepts by using complex graphics. This paper presents some non-trivial examples of the application of the R language from our instruction of the pattern classification course in our school of engineering.